Analisis Keterlambatan Perkembangan dan Kesulitan Belajar pada Siswa Kelas VI Sekolah Dasar : Penelitian - Asry Kusuma Wardani; Indah Lestari; Mochamad Widjanarko (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
This study aims to analyze developmental delay and learning difficulties among sixth-grade elementary school students using a qualitative case study approach. The research subject was a 12-year-old student at SD 1 Undaan Tengah who exhibited significant cognitive developmental delay and academic learning challenges. Data were collected through participatory observation and in-depth interviews with the student’s teacher and parents, and analyzed using the Miles, Huberman, and Saldaña interactive model. The findings reveal that the student’s cognitive delay was primarily caused by biological factors, including neurodevelopmental complications due to oxygen deprivation at birth and prenatal drug exposure. External factors, such as authoritarian parenting and a lack of understanding of special learning needs, further exacerbated the student’s socio-emotional difficulties and self-regulation. These findings reinforce Piaget’s cognitive development theory and Vygotsky’s social constructivist perspective, emphasizing the importance of social support and adaptive learning. The study recommends a psychopedagogical intervention model based on teacher–parent collaboration and the implementation of inclusive education supported by early diagnostic assessment. The results are expected to contribute to the development of a more humanistic and responsive educational policy addressing diverse learning needs in primary education.